STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENERAPKAN PELAYANAN PRIMA DI PERPUSTAKAAN PERGURUAN TINGGI (STUDI KASUS DI PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA) - Aidilla Qurotianti (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
In improving the integrity of an institute or company, needed human resources who satisfy and qualified to be able to advance and develop the institute or company, including the library. Human resources have to give a service excellence to library’s visitors to meet the needs of library’s visitors. But until now still there are librarian who not understand yet the implementation of service excellence in library, so that needed a human resource library development that held by an institute. On of the libraries that implement human resource development is Muhammadiyah University of Yogyakarta’s or UMY Library. UMY Library always endeavor to develop the ability of librarian and library staff to be able to advance the UMY Library to be excellent collage library. The study aim to explain the strategy of human resources library development to implement service excellence at UMY Library. This research use qualitative approach and data collect technic use interview and observation. The result of this research shows that the strategy of human resource that implement at UMY Library are further study of formal education and non formal education, training, rotation, and participation in the activities of librarianship such as scientific meeting, seminar, workshop, the competition of librarian, and call for paper.